Development of Students’ Professional Mobility in Foreign Languages by Pedagogical Conditions - Suyunova Gulchehra Holmamatovna (Genius Journals, 2023)
Pedagogical conditions are conditions that ensure the effectiveness of the pedagogical system and the success of the pedagogical process. Pedagogical conditions mean a set of possibilities, methods, organizational forms and material possibilities of its implementation.
Keywords: Pedagogical activity; conditions; terminological base